2014
DOI: 10.1371/journal.pone.0087137
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Perfluorooctane Sulfonate Affects Glucose Metabolism in Adult Offspring

Abstract: Perfluoroalkyl acids (PFAAs) are globally present in the environment and are widely distributed in human populations and wildlife. The chemicals are ubiquitous in human body fluids and have a long serum elimination half-life. The notorious member of PFAAs, perfluorooctane sulfonate (PFOS) is prioritized as a global concerning chemical at the Stockholm Convention in 2009, due to its harmful effects in mammals and aquatic organisms. PFOS is known to affect lipid metabolism in adults and was found to be able to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 60 publications
5
43
0
Order By: Relevance
“…In our study, PFOS was significantly associated with a steeper upward post load glucose trajectory and prevalent diabetes. This finding is supported by two animal studies showing developmental PFOS exposure may link to impaired glucose metabolism in adulthood (Lv et al, 2013;Wan et al, 2014). Moreover, the observed potential protective effect of PFOA in our study is consistent with a recent animal study, which demonstrated that PFOA may induce insulin hypersensitivity in mice (Yan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, PFOS was significantly associated with a steeper upward post load glucose trajectory and prevalent diabetes. This finding is supported by two animal studies showing developmental PFOS exposure may link to impaired glucose metabolism in adulthood (Lv et al, 2013;Wan et al, 2014). Moreover, the observed potential protective effect of PFOA in our study is consistent with a recent animal study, which demonstrated that PFOA may induce insulin hypersensitivity in mice (Yan et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Experimental studies has shown the obesity-related metabolic effects of PFASs including endocrine disrupting capacity and differential activation of nuclear receptors especially peroxisome proliferator-activated receptors (PPARs) (White et al, 2011). Recent animal studies also support the potential diabetogenic effect of PFASs (Lv et al, 2013;Wan et al, 2014;Wang et al, 2014). Epidemiologic studies investigating the association between PFASs and diabetes are scarce and the results are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Detection in both cord blood and amniotic fluid samples demonstrates that PFOS can also cross the placental barrier, indicating an exposure risk to the developing fetus (Inoue et al, 2004; Toft et al, 2016). Numerous studies have associated PFOS exposures with markers for metabolic syndrome and diabetes, such as elevated insulin and cholesterol, insulin resistance, and altered beta cell function (Lin et al, 2009; Lv et al, 2013; Nelson et al, 2010; Wan et al, 2014). However, the pathological consequences of PFOS exposure for the fetal pancreas, as well as the underlying mechanism of PFOS-induced metabolic dysfunction, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have suggested that intrauterine and perinatal exposure to PFOS may contribute to impaired glucose tolerance and abnormal lipid homeostasis in adulthood (10,11). In humans, prenatal exposure to PFASs has been considered a catalyst of later weight gain in longitudinal studies (12)(13)(14).…”
mentioning
confidence: 99%